Strategies for Improving Multiplication Skills Using Stick Manipulatives Among Second-Grade Elementary School Students in Balikpapan - Amalia Nailoe Rahmah; Ahmad Susanto; Muhamad Sofian Hadi (Faculty of Teacher Training and Education, 2025)
Multiplication skills are fundamental competencies in elementary mathematics education because they provide an essential foundation for understanding more complex mathematical concepts, including fractions, decimals, and algebra. However, many students in the early grades experience difficulties in understanding multiplication as repeated addition and tend to rely primarily on memorizing multiplication tables. These difficulties may affect students’ motivation, self-confidence, and ability to solve contextual problems. This study aimed to examine the effectiveness of using stick manipulatives to improve the multiplication skills of second-grade students in three elementary schools in Balikpapan, representing a public school, a private school, and an Islamic elementary school (Madrasah Ibtidaiyah). The study employed a descriptive qualitative approach, with data collected through pre-tests, post-tests, observations, interviews, and documentation. The findings showed substantial improvement in students’ multiplication skills, with mean scores increasing by more than 25 points and the percentage of students achieving the learning mastery criterion rising from 20–33% to 80–90%. Students also demonstrated greater enthusiasm and active participation during the learning process. Teachers reported that stick manipulatives facilitated the explanation of abstract multiplication concepts and promoted a more interactive classroom environment. These findings indicate that stick manipulatives offer a simple, practical, and effective instructional strategy for strengthening students’ conceptual understanding of multiplication while fostering more positive attitudes toward mathematics.